Espectáculos cortesanos en la América española del siglo XVII : las fiestas como caso para el análisis de la relación entre la Corte y la Corte virreinal (Estudios de Historia de España, 2016)
The Spanish Court of the Austrias, like other Europeans Courts of the 17th Century, organized several kinds of public and private spectacles, such as musical theatre, masquerades, or street parades with allegorical characters, dance and music. They were not only an entertainment but also a way to emphasize the Monarchy’s virtues and to make spectators conscious of their place in this society lead by the King. In Spanish American Colonies, the Viceroy and their courtiers used to imitate those practices. The object was the same: to make present the King’s figure in a distant place, and so to maintain the loyalty to the Crown alive through an entertainment. I analyze two of those spectacles: a masquerade celebrated in Pausa (Perú) and a dramatic-musical intermezzo, celebrated in Sucre. They allow us to know how the Viceroyal Courts and their members followed the behavior of the Madrid courtiers, their social organization, and their way of thinking as a special kind of society.
Keywords: 17th Century; Spanish American Colonies; Courtier Society; Viceroyal Courts; Art and Power; Spectacle; Masquerades; Musical Theatre